The Dynamic Relationship between Good Governance and Economic Growth in Oman (Revista Galega de Economía)
This study aims to examine the dynamic relationship between good governance and economic growth in Oman. The research utilizes financial and macroeconomic data to assess this relationship and test the proposed hypotheses. The data and variables are analysed using Eviews software, employing the autoregressive distributed lag (ARDL) model. The study findings reveal that the Foreign Investment Competitive Index plays a significant moderating role in economic growth, albeit with some negative effects. This research serves as an initial step in formulating effective policies for governing Oman's regions comprehensively. Moreover, it is expected to attract more investors to Oman by advocating stronger cooperative governance across the country. The outcomes of this study hold practical implications for policymakers seeking to foster Oman's economic growth. Additionally, scholars investigating governance and economic expansion can utilize these findings.